PERLINDUNGAN HUKUM PEMANFAATAN SYSTEM ARTIFICIAL INTELLIGENCE BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 - Batubara, Yenni; Ismail, Husni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Artificial Intelligence (AI) with its increasingly complex development currently seems to increase complications, especially when it comes to violations of the law, especially regarding copyright of works created by AI systems or. So that the clarity of the legal responsibility for problems or conflicts that then arise needs to be clarified in the eyes of the law. This study is a qualitative study with a normative legal approach, and the data analysis method used is qualitative juridical. The results of the study show that based on the laws and regulations in Indonesia, namely Law No. 28 of 2014 concerning Copyright and Law No. 12 of 2016 concerning Patents, it states that creators and copyright holders as well as inventors and patent holders are one or several people, meaning that those who have the right to hold copyright and patent rights are humans as legal subjects (persons or legal entities). Then because AI is a system, AI is not included in the legal subject but AI is a human-made product and functions as a tool to create a work. However, formulating clear and fair policies and regulations regarding civil rights and legal responsibility for the results of AI creations needs to be done by the government. Legal certainty in this case will encourage the development of responsible AI technology and provide adequate protection for all parties involved. Then AI is known as an electronic system and electronic agent that operates based on human commands. Therefore, if an unlawful act or action occurs, then the legal responsibility is borne by the creator and user of AI who gives the commands and parameters.